Accounting Students' Interest in the Management Accounting Profession - Ikram, Syafrizal; Rahadian, Irhan (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2026)
Management accounting provides information for managers to plan, control, make decisions, performance evaluation, and has a strategic role in helping organizations achieve operational efficiency as well as sustainable competitive advantage. The purpose of this study is to assess how students perceive the management accounting profession, what factors influence students' interest in management accounting, and how students' interest in management accounting is. The research method uses descriptive analysis, namely to obtain an overview of the conditions, processes, procedures, of a phenomenon being studied. The population of this study is accounting students who have taken or completed Management Accounting courses. The results of the study show that students' perceptions of the management accounting profession in assisting strategic decision-making, value creation, performance management systems and evaluating success. with a good category. Student interest in management accounting, partly driven by encouragement from lecturers and the socialization of information on the management accounting profession. Student interest is due to job opportunities in companies, interest in attending training (seminars) regarding management accounting topics is quite high, but on the other hand, interest in taking certification programs in management accounting is still low and not fully convinced that the field of management accounting has career prospects.